2007
DOI: 10.1002/jcb.21261
|View full text |Cite
|
Sign up to set email alerts
|

Modeled gravitational unloading induced downregulation of endothelin‐1 in human endothelial cells

Abstract: Many space missions have shown that prolonged space flights may increase the risk of cardiovascular problems. Using a three-dimensional clinostat, we investigated human endothelial EA.hy926 cells up to 10 days under conditions of simulated microgravity (microg) to distinguish transient from long-term effects of microg and 1g. Maximum expression of all selected genes occurred after 10 min of clinorotation. Gene expression (osteopontin, Fas, TGF-beta(1)) declined to slightly upregulated levels or rose again (cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 57 publications
9
67
3
1
Order By: Relevance
“…104 Similar effects have also been reported in further studies. 105 More importantly, Ea.hy926 cells readily formed 3D multicellular spheroids similar to those observed on RWVs within the first 24 h of incubation on the RPM. 53,104 Between the 5th and the 7th day of growth on the RPM, double-row cell assemblies were forming.…”
Section: 83mentioning
confidence: 64%
“…104 Similar effects have also been reported in further studies. 105 More importantly, Ea.hy926 cells readily formed 3D multicellular spheroids similar to those observed on RWVs within the first 24 h of incubation on the RPM. 53,104 Between the 5th and the 7th day of growth on the RPM, double-row cell assemblies were forming.…”
Section: 83mentioning
confidence: 64%
“…A recent study showed that ras homolog gene family member A (RhoA) inactivation supports the actin rearrangement-associated angiogenic responses in human umbilical vein endothelial cells (HUVECs) during simulated microgravity [7]. Early cytoskeletal changes of microgravity-exposed ECs have previously been described in real and simulated microgravity [10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when exposed to altered gravity conditions, EC showed strong reactions ranging from alterations in cytoskeletal arrangement and gene expression after only 22 s of real microgravity to long-term effects such as formation of defined 3D structures on the Random Positioning Machine (RPM), a device which aims to simulate microgravity on Earth by randomly rotating the sample around all three axes in space, and thereby cancels out the effect of the gravity vector over time [6,7,8,9,10,11]. Some of these 3D structures assume tubular shapes resembling vascular intimas and recent studies have shown that these structures are a promising basis toward the systematic tissue engineering of vessels [12,13].…”
Section: Introductionmentioning
confidence: 99%